Synthesis and Physical Characterization of PMMA/PP and PMMA/ PAN Composites for Denture Applications - Hassan Sharhan; Zaynab Rasheed; Jawad Oleiwi (Journal of Applied Sciences and Nanotechnology, 2021)
This study involves on manufacture of denture base resin with advanced physical properties through the addition of two type of synthetic fibers used as reinforcing materials polypropylene (PP) and Poly acrylonitrile (PAN). In this research, groups of three samples of both PMMA/PP and PMMA/PAN composites were prepared with the selected fiber weight ratios of 1.5, 3.5, 5.5 and 7.5 %Wt. Physical properties such as water absorption, thermal conductivity and density were evaluated under normal conditions. The chemical bond structure was also investigated for all samples using FTIR test. The results showed that when fibers ratio increased until 7.5 %Wt., the water absorption increases, as well for each fiber which was over 0.6% compared to the 0.3% of the neat sample. A noticeable decrease in the thermal conductivity property from 0.33 W/m.K for PMMA/PP and 0.24 W/m.K for PMMA/PAN comparing to 0.46 W/m. K of the neat polymer was revealed. As for the density results, it was found that when the fibers ratios were increased, the sample density slightly decreased and reached 1.09 g/cm3 for PMMA/PP and 1.1 g/cm3 for PMMA/PAN at the maximum fibers rate. FTIR results indicated there was no new peaks appeared after reinforcement with both fibers. This could refer to the good physical bond between the mixtures, no new material formed.